Sunday

April 20, 2014

April 20, 2014

Posted by **Jay** on Wednesday, January 23, 2013 at 8:14pm.

tan x = tan(x-6pi)

- Trig -
**Reiny**, Wednesday, January 23, 2013 at 9:32pmUsing tan(A-B) = (tanA - tanB)/(1+tanAtanB)

RS = tan(x-6π)

= (tanx - tan 6π)/(1 + tanxtan 6π)

but 6π is coterminal with 2π (6π is 3 rotations, and 2π is one rotation

so tan 6π = tan 2π = 0

= (tanx - 0)/(1+ ) = tanx = LS

so the statement is true

or

tan(-A) = -tanA

so tan(x-6π) = - tan(6π-x)

= -tan(2π-x) , since 6π is coterminal with 2π

= -( -tan(x) ) , by the CAST rule

= tanx

**Related Questions**

Trig - Use reduction identities to determine if the following statement is true ...

Math-Trigonometry - Show that if A, B, and C are the angles of an acute triangle...

Trig. - sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times...

trig - h t t p : / / i m g 4 0 . i m a g e s h a c k . u s / c o n t e n t . p h...

trig - please help me. use trig. identities to find the exact value. tan 25° + ...

trig - please help me. use trig. identities to find the exact value. tan 25° + ...

Trig-Weird Geometry Problem - Determine all triangles ABC for which tan(A-B)+tan...

Trig - tan 15° using composite argument? - tan 15° tan (45°-30°) (tan 45° - tan ...

more trig.... how fun!!!! - if you can't help me with my first question hopw you...

trig - Given that tan 45=1, use tan(x+y) to show that tan 22.5= /2 - 1. (/is ...